Chopin under the sway of George Sand: controversies surrounding the Chopin Festival in Majorca (1930–1936) - Corbera Jaume, Amadeu (Chopin Review, 2025)
The musician and priest Joan M. Thomàs i Sabater (1896–1966) was the promoter of the Chopin Music Festival launched in Majorca in 1931, coinciding with the establishment of the Spanish Republic, to commemorate the Polish musician’s stay on the island during the winter of 1838/39. The event was part of the modernist and Catalanist regeneration programme that, in line with the changing tides in Spain, propelled the intellectualism of Majorca at the time, with the aim of projecting their idea of a modern and European Majorca capable of attracting new visitors. However, the initiative sparked some opposition from conservative Catholics, who did not view favourably Chopin’s rather non-religious figure and his companion on that trip, the writer Aurore Dupin, known as George Sand, questioning why it should be a priest who wished to remember them. Despite the musical success of the Festival during the years of the Republic, controversy resurfaced at the beginning of the Civil War, when Thomàs, then a professor at the Conservatori de Música de Majorca, underwent Francoist purging. Among other accusations, he was charged with wanting to commemorate the journey of Chopin and Dupin and their extramarital relationship. The figures of the pianist and – especially – the writer were seen by the most reactionary elements of the new regime as contrary to the moral values and misogyny of Spanish fascism, and therefore Chopin, in this context, did not deserve to be celebrated.